Sodium doping of Pt/m-ZrO2 promotes C–C scission and decarboxylation during ethanol steam reforming. (17th July 2020) - Martinelli, Michela; Watson, Caleb D.; Jacobs, Gary
Abstract: The effect that sodium has on Pt/m-ZrO2 catalyst was investigated during ethanol steam reforming (ESR). Sodium doping decreases the catalytic activity, but significantly increases CO2 selectivity, providing a means of improving H2 selectivity. Diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) results suggest that acetate species are intermediates in the reaction and that their decomposition can follow different routes depending on the catalyst formulation. When Pt/m-ZrO2 is promoted by sodium, decarboxylation is the favored route: forward decomposition of acetate at lower temperatures yields essentially methane and adsorbed carbonate, further decomposing to carbon dioxide. At higher temperature, the methane precursor can be intercepted by the metal for further steam reforming or a separate methane steam reforming catalyst can be used downstream. Decarbonylation is instead favored for the unpromoted catalyst; decarbonylation tends to lower the H2 selectivity of the overall process. Finally, the addition of sodium promotes C–C scission as methane formation is detected at lower temperature by DRIFTS and TPD-MS of ethanol in steam. This is analogous to formate C–H bond breaking in methanol steam reforming, steam-assisted formic acid decomposition, and water-gas shift reactions. In catalytic testing of ESR utilizing a tubular reactor at low temperatures (where steam reforming of CH4 is limited), methane and CO2 selectivities are higher with the Na-promoted catalyst than with the unpromoted catalyst. Thus, promotion of the forward decomposition of acetate route by Na addition is confirmed. Graphical abstract: Image 1 Highlights: Steam reforming of ethanol on Pt/zirconia involves ethoxy and acetate intermediates. Adding Na electronically modifies the catalyst surface, increasing the basicity. With Na addition, carbon-carbon bond scission occurs at lower T. By adding Na, acetate decarboxylation favored over decarbonylation; H2 selectivity highest. Na addition improves reactivity of a suite of related reactions: WGS, MSR, and ESR.